2013
DOI: 10.4049/jimmunol.1203305
|View full text |Cite
|
Sign up to set email alerts
|

IFIT2 Is an Effector Protein of Type I IFN–Mediated Amplification of Lipopolysaccharide (LPS)-Induced TNF-α Secretion and LPS-Induced Endotoxin Shock

Abstract: Type I IFN signaling amplifies the secretion of LPS-induced proinflammatory cytokines such as TNF-α or IL-6 and might thus contribute to the high mortality associated with Gram-negative septic shock in humans. The underlying molecular mechanism, however, is ill defined. In this study, we report the generation of mice deficient in IFN-induced protein with tetratricopeptide repeats 2 (Ifit2) and demonstrate that Ifit2 is a critical signaling intermediate for LPS-induced septic shock. Ifit2 expression was signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 40 publications
4
53
0
Order By: Relevance
“…Despite nicotine augmented 1.6 and 1.3 folds expression of CD11c and MHC class II, LPS treatment increased about 2.7 and 2.8 folds up-regulation of these molecules, which are in line with previous reports [12], indicating that DCs used in our studies is relatively immature DCs. Apart from immune cells, endothelial cell, fibroblast and other cells were also reported to express IFN-beta and other cytokines in LPS stimulated condition [45][47]. Hence, despite our studies demonstrated that IFN-beta contributes to LPS-induced DCs paralysis, it cannot exclude the possibilities that IFN-beta and other cytokines expressed by other cells facilitate pathogen-induced DCs’ paralysis, which awaits further investigation.…”
Section: Discussionmentioning
confidence: 55%
“…Despite nicotine augmented 1.6 and 1.3 folds expression of CD11c and MHC class II, LPS treatment increased about 2.7 and 2.8 folds up-regulation of these molecules, which are in line with previous reports [12], indicating that DCs used in our studies is relatively immature DCs. Apart from immune cells, endothelial cell, fibroblast and other cells were also reported to express IFN-beta and other cytokines in LPS stimulated condition [45][47]. Hence, despite our studies demonstrated that IFN-beta contributes to LPS-induced DCs paralysis, it cannot exclude the possibilities that IFN-beta and other cytokines expressed by other cells facilitate pathogen-induced DCs’ paralysis, which awaits further investigation.…”
Section: Discussionmentioning
confidence: 55%
“…In murine macrophages, overexpression of IFIT2 represses lipopolysaccharide (LPS) induced TNF- α and IL-6 expression [65]. In contrast, IFIT2 −/− mice display reduced TNF- α and IL-6 in serum and LPS-mediated lethality in an endotoxic shock model, suggesting IFIT2 is a critical mediator for the secretion of LPS-induced proinflammatory cytokines [66]. In C. trachomatis , both IFIT1 and IFIT2 genes were reported to be up-regulated more than 10 fold in HeLa 229 cells by 16 hpi [67].…”
Section: Discussionmentioning
confidence: 99%
“…A specific cytokine, IFN-β, induced by TLR4 signaling, is associated with TLR4-mediated sepsis (41). An ISG, Ifit2, has recently been shown to be a potential effector of TLR4-mediated sepsis (42). The expression of TLR3 and TLR4 in intestinal epithelium is altered in active IBD and specific polymorphism in the TLR4 gene has been associated with Crohn’s disease and ulcerative colitis (43).…”
Section: The Role Of Tlrs In Pathogenesismentioning
confidence: 99%